Effects Of Chitosan Treatment On The Quality Parameters Of Shrimp (Parapenaeus Longirostris) During Chilled Storage - Bingol, Enver Baris; Bostan, Kamil; Varlik, Candan; Uran, Harun; Alakavuk, Didem Ucok; Sivri, Nuket (Aperta, 2015)
This study was conducted to investigate the effects of chitosan treatment on the quality criteri as of shrimps for a long time "in chilled" storage. Fresh deepwater pink shrimps (Parapenaeus longirostris), caught from Marmara Sea were dipped in different solutions containing the combinations of sodium metabisulphite (2500 mg/L), 4-hexylresorcinol (50 mg/L), chitosan (5 g/L), citric acid (200 mg/L) and rosemary extract (50 mg/L) for ten minute, over-wrapped in styrofoam plates and stored at 4 degrees C for six days. During the storage period, pH, microbiological counts of total aerobic mesophilic bacteria (TAMB), total psychrotrophic bacteria (TPB), lactic acid bacteria (LAB), Pseudomonas spp. and Enterobacteriaceae, instrumental texture (shear force), moisture, TVB-N, TMA-N and sensory characteristics of shrimps were evaluated. TVB-N and TMA-N amounts in shrimps treated with polyphenol oxidase inhibitors alone are significantly higher than treated with chitosan throughout storage. Reduction in odor and flavour scores of chitosan treated samples was more slowly than others, while rosemary extract addition caused an undesirable flavor changes in shrimps. Coating with chitosan reduced moisture loss, textural softening and increase in pH of shrimps. The microbial counts of shrimps were gradually increase during storage, but addition of chitosan reduced the growth of spoilage bacteria and showed further inhibitory effect than samples treated with only antimelanosis agents. Incorparating of citric acid and rosemary extract into dipping solutions containing chitosan were inadequate to meet the commercial expectation. As a result, shrimps coated with chitosan after capture can provide an increase of up to twice the shelf-life by slowing down the biochemical reactions during cold storage.